National Antiretroviral Access for People with HIV/AIDS, the Extension Phase to Reach Uninsured and Limited Rights Patients - แทนประเสริฐสุข สมบัติ; ชาสมบัติ สัญชัย; ยุกตานนท์ พรทิพย์; ก้องสกุลไกร ณัฐพร; เกษธรรม กมล (Disease Control Journal, 2012)
Thailand initiated a project to provide ART to people with HIV/AIDS who were un-insured and with limited rights, mostly non-Thai immigrants, in 2006. The project was partially supported by the Global Fund with a target of 2,000 cases. From October 2006 to September 2011, there were 6,148 cases cumulatively received service for the project. Of these, 4,414 cases (71.8 °/o) were non-Thai targeted patients, and 1,734 (28.2 °/o) were Thais. At enrollment, 51.82 °/o of targeted and 37.77 °/o of Thai patients had CD4 cell count equal to or less than 200 cell/mm3. 68.4 °/o of targeted and 37.77 °/o of Thai patients had never received ART before. In September 2011, there were 2,834 targeted cases (64.2 °/o of cumulative targeted patients) and 217 cases of Thais (12.5 °/o of cumulative Thai patients) actively participated in the project. Number of cases treated with first-line regimen among targeted and Thai patients were 2,564 (90.5 °/o) and 165 (76.0 °/o) respectively. ART services provided in this project had been developed based on humanitarian reason in order to reduce morbidity and mortality related to HIV and AIDS. Challenges and recommendations for future development included: (1) Financial support from GFATM would end in 2014, therefore, the provision of sustainable ART service for this targeted patient should be developed. (2) For future plan, attempt to estimate number of needed cases should be made in order to request sufficient resources to implement project. (3) Thai patients were enrolled due to gap during changes in health insurance scheme or fear of losing confidentiality, however, with explanation on the objective of the project, almost Thai cases had been referred out. (4) Since there had been a number of losses to follow up, there should be a study to identify more appropriate means to retain cases for long-term treatment programme.